Noise Performance of Heterojunction DDR MITATT Devices Based on at W-Band - Suranjana Banerjee; Aritra Acharyya; J. P. Banerjee (Active and Passive Electronic Components)
Noise performance of different structures of anisotype heterojunction double-drift region (DDR) mixed tunneling and avalanche transit time (MITATT) devices has been studied. The devices are designed for operation at millimeter-wave W-band frequencies. A simulation model has been developed to study the noise spectral density and noise measure of the device. Two different mole fractions and of Ge and corresponding four types of device structure are considered for the simulation. The results show that the -Si heterojunction DDR structure of MITATT device excels all other structures as regards noise spectral density ( sec) and noise measure (33.09 dB) as well as millimeter-wave properties such as DC-to-RF conversion efficiency (20.15%) and CW power output (773.29 mW).